Technological Advocacy and Crime Reporting in an HBCU Setting: Addressing the Prospect of Legal Cynicism in the Ebony Tower. (March 2022) - Webb, Patrick; Chin, Jason; Williams, Cynthia-Lee; Dennis, Kimya
In comparison to white students, the study of Black student attitudes toward crime reporting on college campuses is deficient, especially in historically Black colleges and universities (HBCUs). Using approximately 100 completed student questionnaires, statistical results suggest that the majority of students express a willingness to report a campus-related crime to campus police. The highest reported explanation for refusing to report a crime is based upon the prospect of being labeled in a negative manner. The highest reported explanation for reporting a crime is based upon the receipt of a financial reward and anonymity. Bivariate calculations indicate that age, gender, and residential status are significantly associated with crime reporting decisions. Policy implications, areas of further research, and limitations are provided.